Peran Kurikulum dalam Pendidikan Anak Usia Dini - Arsy; Novita Loka (Program Studi Pendidikan Islam Anak Usia Dini, 2026)
The PAUD curriculum functions as a guide that directs the learning process at an early age with the aim of optimizing children's potential in various aspects of development. Education at this stage does not only focus on achieving academic abilities, but also includes the development of character, social skills and moral values that will shape the child's personality in the future. A good PAUD curriculum has a very strategic role in forming the foundations of children's development, both in physical, mental and social aspects. This research uses the Miles and Huberman approach research methods, namely data reduction, presenting narratives and drawing conclusions. A holistic approach is able to see a child's development for both cognitive and academic purposes only. This approach aims to support children to develop optimally in all dimensions of life. The PAUD curriculum has an important role in supporting children's development in the early stages of their lives. Apart from that, the role of parents is also very important in guiding and supervising children's development.